Application of Image Analysis in Food Grain Quality Inspection and Evaluation During Bulk Storage - Aviara, N. A.; Adesanya, A. A.; Iyilade, I. J.; Olorunsola, E. O.; Oyeniyi, S. K. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2022)
With increased expectations for high quality food products and safety standards, the need for accurate, fast and objective quality determination of moisture, purity, germination and pathogen free food products and grains during bulk storage continues to grow. This paper reviews the application of image analysis in food grain quality inspection and discusses the potential of the technology for application in grain quality monitoring and evaluation during bulk storage. Image analysis procedure and physical properties of the grain bulk were also discussed. Image analysis is an automated alternative to manual inspection with less processing time and more accurate results. Human inspection has been found wanting due the bias judgment and results. Image analysis of food grains during bulk storage can only get better with its diverse applications in varietal identification, distinctness, uniformity and stability (DUS) testing, detection of insects and foreign bodies within the grain bulk and the detection of hot spot in the bin to mention a few. In Nigeria, image analysis will be a great tool in terms of grain quality preservation in National Grain Reserves (NGRs), providing seeds for farmers for the next planting season and reviving the grain reserves in Nigeria to boost gainful employment of citizens. An automated grain reserves using image analysis is possible in Nigeria only if appropriate government policies and funding can throw its full weight behind the innovation.